Glossing Over: How Magazine Fact Checkers Use Conditional Self-Presentation to Straddle Glamour and Dreariness in Their Work (Journal of Organizational Psychology, 2020)
In this paper, we introduce the concept of Glossy Work, work that has a glamorous patina but that is actually mundane and unfulfilling. We studied magazine fact checkers, who exemplify Glossy Work, specifically examining how they balance these discrepant aspects of the job in presenting their work to others. We found that fact checkers use conditional presentation to modulate their portrayal of the work according to audience members’ knowledge of their job’s secret taint and the nature of presenter’s relationship to that audience. Presentations ranged from full disclosure to deliberate attempts to reframe the presentation to unfettered job enhancement.
Keywords: Organizational Psychology; self-enhancement; presentation; self-verification; concept of Glossy Work